A neuroimaging dataset during sequential color qualia similarity judgments with and without reports - Takahiro Hirao; Mitsuhiro Miyamae; Daisuke Matsuyoshi; Ryuto Inoue; Yuhei Takado; Takayuki Obata; Makoto Higuchi; Naotsugu Tsuchiya; Makiko Yamada (Scientific Data)
Abstract Recent neuroscientific research has advanced our understanding of consciousness, yet the connection between specific qualitative aspects of consciousness, known as “qualia,” and particular brain regions or networks remains elusive. Traditional methods that rely on verbal descriptions from participants pose challenges in neuroimaging studies. To address this, our group has introduced a novel “qualia structure” paradigm that leverages exhaustive, structural, and relational comparisons among qualia instead of verbal reports. In this study, we present the fMRI dataset that captures relational similarity judgments among two out of nine color qualia per trial from 35 participants. This dataset also includes a “no-report” condition in half of the trials to assess the impact of overt reporting. Additionally, each participant’s color discriminability was evaluated with a hue test conducted outside the scanner. Our data offer valuable insights into the brain functions associated with color qualia and contribute to a deeper understanding of the neural foundations of consciousness.